Operations in Synthesized Eight Link Gear Variable Topology Mechanism using Python Programming - Daivagna, Umesh M (International Journal of Scientific Research in Mechanical and Materials Engineering, 2022)
This paper illustrates the implementation of python programming in the field of kinematics and helps the planners to visualize the working nature of the synthesized mechanism. In the present context, the authors have considered eight link gear variable topology mechanism in this paper which is synthesized using a complex number approach. This synthesized mechanism is studied using MATLAB programming and the various positions obtained are taken into the consideration for python programming. These advanced tools create an insight among the design engineers on the working nature of the mechanism. The operating condition of the synthesized eight link gear variable topology mechanism in two different phases is analyzed using python programming. This shows the mechanism operating condition in two different phases and validates the output obtained with the help of visualization results in mechanism orientation.
uGDX
Keywords: Variable Topology Mechanism; Python Programming; Synthesized Eight Link Gear Mechanism